caracterização in situ e estrutura genética de populações de Gossypium mustelinum - Alves, Milena Ferreira (2009)
Gossypium mustelinum Miers ex Watt is the only cotton species native from Brazil. It is endemic of the semi-arid region from North-east of the country, where it occur near from resilient water sources. The threats to the in situ conservation of the populations are caused by human interference in its habitat, mainly by excessive cattle graze and deforestation. Establish efficient strategies of in situ conservation depend on the accomplishment of a diagnosis of how the specie is found in its natural environment, and the knowledge about the genetic structure of the populations. The objectives of this work were i) to determine the in situ conditions of two populations present in rivers from basin of Rio Paraguaçu at the Bahia State, ii) to evaluate the structure and genetic variability presented in both populations, iii) to establish in situ and ex situ conservation strategies. It were realized collection in november 2007, when was realized in situ characterization of G. mustelinum. SSR markers were used for analyze 218 genotypes deriving from two populations of the G. mustelinum, localized at Tocó river and the Capivara river. The allelic frequencies, the heterozigosity and the F statics were estimated. All the plants were classified as wild and natives, and there was no evidence of the use the plants or its parts. The populations showed different conservation conditions in situ. Few plantlets were found in sites with excessive cattle feed, an indication that the damages in young plants should be high enough to compromise the renovation of the populations. On the other hand, populations were well preserved when the anthropic damages was low or inexistent. The 14 SSR primer pairs amplified 17 loci with a medium number of 5 alleles per locus (a total of 85 alleles). The high level of endogamy estimated (FIS=0,808) and the low observed heterozygosity (H0=0,093) were indicatives that the populations reproduce mainly by selfing, geitonogamy and crosses between related individuals. The genetic diversity was high (HE=0,482) and the differentiation between the populations was very high (FST=0,328). At least two sites from both populations of G. mustelinum must be preserved to achieve suitable in situ conservation. Actions that preserve the gallery forest and keep the cattle away should implemented, and could be as simple as erecting a fence. It is not possible anticipated if the in situ preservation will be possible. Therefore collections and ex situ preservation of representative specimens are essential to conserve the genetic diversity of native G. mustelinum